2013
DOI: 10.1152/physiolgenomics.00099.2012
|View full text |Cite
|
Sign up to set email alerts
|

New quantitative trait loci for carotid atherosclerosis identified in an intercross derived from apolipoprotein E-deficient mouse strains

Abstract: Carotid atherosclerosis is the primary cause of ischemic stroke. To identify genetic factors contributing to carotid atherosclerosis, we performed quantitative trait locus (QTL) analysis using female mice derived from an intercross between C57BL/6J (B6) and BALB/cJ (BALB) apolipoprotein E (Apoe−/−) mice. We started 266 F2 mice on a Western diet at 6 wk of age and fed them the diet for 12 wk. Atherosclerotic lesions in the left carotid bifurcation and plasma lipid levels were measured. We genotyped 130 microsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(55 citation statements)
references
References 60 publications
(74 reference statements)
12
42
1
Order By: Relevance
“…Similar findings have been observed with other mouse crosses [15,23,30]. These findings are consistent with the observation made from Mendelian randomization studies of HDL for role in human coronary heart disease [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings have been observed with other mouse crosses [15,23,30]. These findings are consistent with the observation made from Mendelian randomization studies of HDL for role in human coronary heart disease [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…In the case of CHOL190, heterozygous individuals displayed lower means than the 2 homozygous genotypes. This pattern of underdominance is difficult to explain from a functional perspective because the molecular basis of dominance is not yet fully understood, but similar results have been obtained in mouse, where underdominant QTL for serum lipids (Lawson et al, 2010) and carotid atherosclerosis (Rowlan et al, 2013) have been reported so far. Previous data obtained in humans provided evidence that adiponectin levels are negatively correlated with LDL concentrations (Kantartzis et al, 2006) and LDL particle size (Lara-Castro et al, 2006).…”
Section: Resultsmentioning
confidence: 76%
“…Bglu17 on Chr9 has been mapped in 3 separate intercrosses, including previously reported C57BLKS x DBA/2 [ 35 ] and B6- Apoe −/− x BALB- Apoe −/− crosses [ 21 ]. Hdlq17 on Chr9 has been mapped in multiple crosses, including B6 x 129, B6 x CAST/EiJ, B6- Apoe −/− x C3H- Apoe −/− , and B6- Apoe −/− x BALB- Apoe −/− crosses [ 24 , 27 , 31 , 32 , 36 38 ]. We conducted haplotype analyses using Sanger SNP database to prioritize positional candidate genes for both QTLs.…”
Section: Resultsmentioning
confidence: 99%